Germline SUCLG2 Variants in Patients With Pheochromocytoma and Paraganglioma - Hadrava Vanova, Katerina; Pang, Ying; Krobova, Linda; Kraus, Michal; Nahacka, Zuzana; Boukalova, Stepana; Pack, Svetlana D; Zobalova, Renata; Zhu, Jun; Huynh, Thanh-Truc; Jochmanova, Ivana; Uher, Ondrej; et al. (Journal of the National Cancer Institute, 2022)
BACKGROUND: Pheochromocytoma and paraganglioma (PPGL) are neuroendocrine tumors with frequent mutations in genes linked to the tricarboxylic acid cycle. However, no pathogenic variant has been found to date in succinyl-CoA ligase (SUCL), an enzyme that provides substrate for succinate dehydrogenase (SDH; mitochondrial complex II [CII]), a known tumor suppressor in PPGL. METHODS: A cohort of 352 patients with apparently sporadic PPGL underwent genetic testing using a panel of 54 genes developed at the National Institutes of Health, including the SUCLG2 subunit of SUCL. Gene deletion, succinate levels, and protein levels were assessed in tumors where possible. To confirm the possible mechanism, we used a progenitor cell line, hPheo1, derived from a human pheochromocytoma, and ablated and re-expressed SUCLG2. RESULTS: We describe 8 germline variants in the guanosine triphosphate-binding domain of SUCLG2 in 15 patients (15 of 352, 4.3%) with apparently sporadic PPGL. Analysis of SUCLG2-mutated tumors and SUCLG2-deficient hPheo1 cells revealed absence of SUCLG2 protein, decrease in the level of the SDHB subunit of SDH, and faulty assembly of the complex II, resulting in aberrant respiration and elevated succinate accumulation. CONCLUSIONS: Our study suggests SUCLG2 as a novel candidate gene in the genetic landscape of PPGL. Large-scale sequencing may uncover additional cases harboring SUCLG2 variants and provide more detailed information about their prevalence and penetrance.
Keywords: zárodečné mutace; nádory nadledvin; Paraganglioma; Germ-Line Mutation; Humans; Succinate Dehydrogenase; paragangliom; lidé; Adrenal Gland Neoplasms; Pheochromocytoma; feochromocytom; sukcinátdehydrogenasa